Influence of hand grip strength test and short physical performance battery on FRAX in post-menopausal women: a machine learning cross-sectional study - de Sire, Alessandro; Marotta, Nicola; Prestifilippo, Emanuele; Calafiore, Dario; Lippi, Lorenzo; Sconza, Cristiano; Muraca, Lucia; Invernizzi, Marco; Mezian, Kamal; Ammendolia, Antonio (Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Impaired physical performance and muscle strength are recognized risk factors for fragility fractures, frequently associated with osteoporosis and sarcopenia. However, the integration of muscle strength and physical performance in the comprehensive assessment of fracture risk is still debated. Therefore, this cross-sectional study aimed to assess the potential role of hand grip strength (HGS) and short physical performance battery (SPPB) for predicting fragility fractures and their correlation with Fracture Risk Assessment Tool (FRAX) with a machine learning approach. METHODS: In this cross-sectional study, a group of postmenopausal women underwent assessment of their strength, with the outcome measured using the HSG, their physical performance evaluated using the SPPB, and the predictive algorithm for fragility fractures known as FRAX. The statistical analysis included correlation analysis using Pearson's r and a decision tree model to compare different variables and their relationship with the FRAX Index. This machine learning approach allowed to create a visual decision boundaries plot, providing a dynamic representation of variables interactions in predicting fracture risk. RESULTS: Thirty-four patients (mean age 63.8±10.7 years) were included. Both HGS and SPPB negatively correlate with FRAX major (r=-0.381, P=0.034; and r=-0.407, P=0.023 respectively), whereas only SPPB significantly correlated with an inverse proportionality to FRAX hip (r=-0.492, P=0.001). According to a machine learning approach, FRAX major ≥20 and/or hip ≥3 might be reported for an SPPB<6. Concurrently, HGS<17.5 kg correlated with FRAX major ≥20 and/or hip ≥3. CONCLUSIONS: In light of the major findings, this cross-sectional study using a machine learning model related SPPB and HGS to FRAX. Therefore, a precise assessment including muscle strength and physical performance might be considered in the multidisciplinary assessment of fracture risk in post-menopausal women.
Keywords: síla ruky; Hand Strength; hodnocení rizik; Female; tělesná a funkční výkonnost; ženské pohlaví; průřezové studie; postmenopauza; kostní denzita; Bone Density; lidé; Osteoporotic Fractures; Risk Assessment; Risk Factors; Cross-Sectional Studies; Aged; rizikové faktory; Physical Functional Performance; lidé středního věku; osteoporotické fraktury; senioři; Postmenopause; Middle Aged; Humans